2015
DOI: 10.1371/journal.pone.0136249
|View full text |Cite
|
Sign up to set email alerts
|

Co-Flocculation of Yeast Species, a New Mechanism to Govern Population Dynamics in Microbial Ecosystems

Abstract: Flocculation has primarily been studied as an important technological property of Saccharomyces cerevisiae yeast strains in fermentation processes such as brewing and winemaking. These studies have led to the identification of a group of closely related genes, referred to as the FLO gene family, which controls the flocculation phenotype. All naturally occurring S. cerevisiae strains assessed thus far possess at least four independent copies of structurally similar FLO genes, namely FLO1, FLO5, FLO9 and FLO10. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 44 publications
(52 reference statements)
4
39
0
1
Order By: Relevance
“…In particular, the significant difference with respect to terms related to flocculin repeats, found in lectin-like proteins, and flocculation (Flo11) observed in H2 and H4 strains is an intriguing and industrially relevant trait (Tables 5, 6). Flocculation, the process by which yeast cells spontaneously aggregate to form flocs with sediment in the culture, has been observed in different yeast species, including non-Saccharomyces isolates and H. uvarum (Rossouw et al, 2015). Beyond its physiological relevance as a protective mechanism to enhance the survival under environmental stresses (Marika et al, 1993), flocculation is a desirable technological feature allowing the separation of cells from media in fermentation processes such as brewing and winemaking (Pretorius, 2000;Soares, 2011), in particular sparkling wine obtained by the so-called Method Champenoise.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the significant difference with respect to terms related to flocculin repeats, found in lectin-like proteins, and flocculation (Flo11) observed in H2 and H4 strains is an intriguing and industrially relevant trait (Tables 5, 6). Flocculation, the process by which yeast cells spontaneously aggregate to form flocs with sediment in the culture, has been observed in different yeast species, including non-Saccharomyces isolates and H. uvarum (Rossouw et al, 2015). Beyond its physiological relevance as a protective mechanism to enhance the survival under environmental stresses (Marika et al, 1993), flocculation is a desirable technological feature allowing the separation of cells from media in fermentation processes such as brewing and winemaking (Pretorius, 2000;Soares, 2011), in particular sparkling wine obtained by the so-called Method Champenoise.…”
Section: Discussionmentioning
confidence: 99%
“…The flocculation characteristics of yeast are strongly strain-dependent and largely defined by which members of the FLO genes, which encode for lectin proteins, are functional in each strain. Rossouw et al [36] showed that for 17 out of 18 investigated, non-Saccharomyces strains the flocculation phenotypes were calcium-dependent, thus indicating a FLO-dependency much like in Saccharomyces cerevisiae.…”
Section: Yeast Characterizationmentioning
confidence: 99%
“…Recent data suggest that such biotic impacts may be significant and that their role in defining population dynamics and fermentation outcomes may have been underestimated. A number of recent articles, for instance, suggest that physical contact between species has significant impact on the performance of these species 37,38 . The data by Rossouw et al 38 suggest that modifying the level of physical contact will lead to complex changes in population dynamics, either favouring or inhibiting certain species.…”
mentioning
confidence: 99%